2019
DOI: 10.1136/bmjopen-2019-031176
|View full text |Cite
|
Sign up to set email alerts
|

Urban scaling of health outcomes: a protocol for a scoping review

Abstract: IntroductionWith most of the world’s population living in urban areas, it is important to understand the health effects of city living. Precise descriptions of the relations of city size and growth with population health metrics have not been systematically described. Describing these relationships can provide clues regarding the factors driving differences in health across cities.ObjectiveThe goal of this scoping review is to map the existing evidence regarding the scaling properties of health outcomes, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Physical conditions were assessed with proxies for urban growth, measures of the size and density of the area. Urban growth has been proposed as a relevant factor for health and wellbeing processes in cities [ 25 , 26 ]. The municipal area corresponds to the total surface area of the municipality in km 2 , according to the National Geostatistical Framework [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Physical conditions were assessed with proxies for urban growth, measures of the size and density of the area. Urban growth has been proposed as a relevant factor for health and wellbeing processes in cities [ 25 , 26 ]. The municipal area corresponds to the total surface area of the municipality in km 2 , according to the National Geostatistical Framework [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that many domestic and foreign studies emphasize the predominant role of the environmental factor as one of the main determinants of public and individual health [6]. This was also confirmed by the results of focus group interviews, during which, answering the question "What do you think, what factors have the greatest impact on human health?"…”
Section: Resultsmentioning
confidence: 66%
“…We followed the framework of the Joanna Briggs Institute (JBI) [15] and reported methods and results using the Preferred Reporting Items for Systematic Review and Meta-Analysis Extension for Scoping Reviews (PRISMA ScR) guidelines [16]. More details on the scoping review methodology can be found in the review protocol [17].…”
Section: Methodsmentioning
confidence: 99%